Picrotoxin- and 4-aminopyridine-induced activity in hilar neurons in the guinea pig hippocampal slice - Müller, Wolfgang; Misgeld, Ulrich (Journal of neurophysiology, 1991)
1. Paired extra- and intracellular recording was used to study the activity of neurons in the dentate hilus and their interaction with CA3/CA4 pyramidal neurons and granule cells during picrotoxin- or 4-aminopyridine (4-AP)-induced rhythmical activity in the guinea pig hippocampal slice. 2. Picrotoxin induced synchronous repetitive population spikes in the CA3, CA4, and hilar region, but no extracellular activity in the granule cell layer. 4-AP induced rhythmically occurring positive field-potential waves in the CA3, CA4, and granular layer coincident to negative/positive field potentials in the hilus. 3. Picrotoxin-induced activity originated in the CA3 area and subsequently appeared in the CA4 and hilar region, whereas 4-AP-induced activity appeared simultaneously in all subfields. 4. Blockade of fast glutamatergic excitation by 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX, 10 microM) blocked the picrotoxin-induced activity but not the 4-AP-induced activity. 5. Focal application of tetrodotoxin (TTX) between area CA3 and CA4 blocked picrotoxin-induced activity in the CA4 and hilar region but decoupled 4-AP-induced activity in the CA3 area. 6. Under intracellular recording, picrotoxin induced bursts in CA3, CA4, and hilar neurons but K-dependent slow IPSPs in granule cells. 4-AP induced rhythmically occurring burst in hilar neurons synchronous to Cl- and K-dependent IPSPs in CA3, CA4, and granule cells. 7. Comparison of picrotoxin- and 4-AP-induced rhythmical burst activity reveals that many hilar neurons are excited by CA3/CA4 pyramidal neurons in addition to the well-known excitation by granule cells and perforant path fibers, and that, in turn, many hilar neurons inhibit CA3, CA4, and granule cells.